Sutemos. - Jansas, Evaldas; Jutempus; Kuizinas, Kestutis; Narkevicius, Deimantas; Rodgers, Kathleen; Warr, Tracey (Vilnius : Contemporary Art Centre, 1998)
Ceponyte, Aida ; Ozarinskas, Valdas ; Carbaciauskas, Algis ; Gilchrist, Bruce ; Jansas, Evaldas ; Urbonas, Cediminas ; Urboniene, Nomeda ; Jutempus ; Cluta, Darius ; Koester, Joachim ; Kumetaitis, Giedrius ; Ratavicius, Mindaugas ; Tarvydas, Simonas ; Lislegaard, Ann ; Maceina, Algimantas ; Makarevicius, Cintaras ; Martin, Rosemarie ; Mazylis, Saulius ; Novickas, Audrius ; Raila, Arturas ; Rakauskaité, Eglé ; Rogers, Kathleen ; Andrijauskas, Tomas ; SODA ; Cernauskas, Vladas ; Zvybas, Donaldas ; Stanevicius, Helmantas ; Spokauskas, Mindaugas ; Wallin, Magnus ; Visser, Barbara ; Birtun, Lars Wellejus ; Navakas, Mindaugas ; Wilson, Jane & Louise ; Zaltauskas, Vytautas
biografie
Sutemos / Twilight, Contemporary Art Centre, Vilnius, 1998.01.20 - 02.22
Engels & Litouws
kunstcatalogus